Reproductive disorders in bitches - DEKA, H M; PANDIT, R K; SRIVASTAVA, O P; BHATT, V K (The Indian Journal of Animal Reproduction, 2005)
Of the 3954 bitches presented at the college hospital during 1993-2002 77.60% were treated for the general conditions.The reproduction related cases included 5% for the pregnancy diagnosis, 3.41 % ovario-hysterectomised and 1.45% bitches werepresented during estrus. Amongst the reproductive diseases most frequent were 3.82% venereal granuloma, 3.40% pyometra, 2.07%mammary tumor, 1.45% dystocia, 0.86% ascites, 0.71 % abortion and 0.23% prolapsing genitalia.
Keywords: Reproductive disorders; bitches